Increased sensitivity and high specificity of indirect immunofluorescence in detecting IgG subclasses for diagnosis of bullous pemphigoid. (1st April 2018) - Jankásková, J.; Horváth, O. N.; Varga, R.; Arenberger, P.; Schmidt, E.; Ruzicka, T.; Sárdy, M.
Summary: Background: Indirect immunofluorescence (IIF) microscopy on monkey oesophagus is an important assay for the diagnosis of bullous pemphigoid (BP). Its relatively low sensitivity (60–80%) may be partly due to insufficient detection of minor IgG subclasses. Aim: To determine the operating characteristics of an IgG subclass in IIF. Methods: We designed a retrospective, dual‐centre, controlled cohort study on sera from 64 BP sera that had been rated as false negatives by traditional IIF microscopy, and assessed circulating IgG1, IgG3 and IgG4 autoantibodies. Results: The sensitivities of IIF in detecting IgG1, IgG3, IgG4 and all three in combination were 45.3%, 18.8%, 32.8% and 48.4%, respectively. Specificities were > 97%. Conclusion: Detection of IgG subclass (especially IgG1 and IgG4 ) autoantibodies by IIF on monkey oesophagus can significantly improve diagnostic performance of IIF microscopy for diagnosis of BP.